Supramolecular design of hydrophobic and hydrophilic polymeric nanoparticles - Ferreira, Leonardo M.B. [UNESP]; Kiill, Charlene P. [UNESP]; Pedreiro, Liliane N. [UNESP]; Santos, Aline M. [UNESP]; Gremião, Maria Palmira D. [UNESP] (Elsevier, 2018)
Supramolecular design refers to the application of supramolecular chemistry concepts and tools to the development of drug delivery systems. The approach is explored in this chapter in the context of nanomanipulation of polymer-based systems. Fundamental aspects of supramolecular interactions are discussed, focusing on their importance to the fabrication of hydrophobic and hydrophilic nanoparticles. Specific discussion explores the self-assembly process of polymer building blocks in polymeric nanoparticles and the main tools and techniques used to monitor synthetic procedures and characterize physicochemical properties. The chapter ends with the major challenges that should be addressed to optimize self-assembly for rational design of polymer-based nanoparticles.
Keywords: hydrophilic nanoparticles; hydrophobic nanoparticles; nanomanipulation; polymeric nanoparticle; rational design; self-assembly; Supramolecular chemistry; supramolecular interactions